2014
DOI: 10.1097/mat.0000000000000128
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Tissue Oxygenation During the Initiation of Venovenous ECMO

Abstract: median (interquartile range). The cerebral rSO2 increased significantly (p < 0.05) from 69(61-74) to 75(60-80)% after ECMO was started, concomitant to the arterial oxygenation. Until the end of the observation period after 83(44-132) minutes, cerebral rSO2 decreased significantly to 61(52-71)%. PaCO2 decreased from 70(61-87) to 43(38-54) mm Hg and the pH increased from 7.23(7.14-7.29) to 7.39(7.34-7.43). The baseline arterial oxygen saturation and tension as well as the actual bicarbonate concentration were ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 29 publications
0
23
1
Order By: Relevance
“…Recently, Muellenbach et al reported that patients receiving vvECMO treatment were at risk for a decrease in cerebral regional tissue oxygen saturation at ECMO initiation, and that this decreased is linked to PaCO2 change. This could be involved in the pathogenesis of brain injury of ECMO patients [19,20]. In our study, the acute PaCO 2 change was independently associated with cerebral bleeding and one can hypothesize that these abrupt changes may have facilitated brain hemorrhages.…”
Section: Discussionmentioning
confidence: 48%
“…Recently, Muellenbach et al reported that patients receiving vvECMO treatment were at risk for a decrease in cerebral regional tissue oxygen saturation at ECMO initiation, and that this decreased is linked to PaCO2 change. This could be involved in the pathogenesis of brain injury of ECMO patients [19,20]. In our study, the acute PaCO 2 change was independently associated with cerebral bleeding and one can hypothesize that these abrupt changes may have facilitated brain hemorrhages.…”
Section: Discussionmentioning
confidence: 48%
“…Increased CO 2 levels are known to have a variety of effects on the human body, including changes in vascular regulation, especially cerebral and pulmonary perfusion, renal function, and cardiac and immunological functions. [82][83][84] Kielstein et al assumed that the mitigation of respiratory acidosis caused by ECMO may improve renal function. However, in a retrospective, single center study, patients who required ECMO therapy but no renal replacement showed no reduction in elevated serum creatinine after 1 day of treatment as compared with the day of ECMO implantation.…”
Section: Influence Of Long-term Lung Support On Pathophysiologymentioning
confidence: 99%
“…Hypercapnia is common before ECLS initiation, and a large decrease in PaCO 2 with ECMO initiation may cause cerebral vasoconstriction, with a resulting decrease in brain tissue oxygen supply. [84][85][86] Low sweep GF should be used initially to slowly correct hypercapnia, and the minute ventilation of the native lung should be decreased immediately. The PaCO 2 target of EOLIA was <45 mm Hg.…”
Section: Mechanical Ventilation During Vv-eclsmentioning
confidence: 99%